Ethical Discourse of Medical Students on the Phenomenon of Death: A Qualitative Study - Keleş, Şükrü; Gül, Şenay; Yıldız, Abdullah; Karabulut, Seyhan Demir; Eren, Handan; İskender, Mahinur Durmuş; Baykara, Zehra Göçmen; Yalım, Neyyire Yasemin (SAGE Publications, 2021)
The aim of this study is to discover medical students’ ideas on the phenomenon of death; produce information on how these students interpret the value-related problems regarding death that they come across in different units of hospitals; and assess this data in ethical terms. This study included a qualitative research in which 12 focus group interviews were conducted with 92 fifth- and sixth-year medical students. Data obtained from interviews were assessed using a thematic content secondary analysis. The main themes were specified according to the medical students’ statements and were reviewed under the contexts of the “dying process”; “effects of death”; “attitude and behavior of health professionals”; “seeing a dead body/looking at a dead body”; “accepting death”; and “forms of expressions of death.” Medical students’ encounters with death in different units of hospitals leads them to question their values and familiarize themselves with the borders of their areas of profession.
Keywords: Students, Medical; Attitude to Death; Attitude of Health Personnel; Humans; Focus Groups; Qualitative Research; 4. Education; 16. Peace & justice; 3. Good health